(untitled) (American & British Studies Annual, 2011)
Combining translation and linguistic studies, the article introduces two less-known immigrant writers Romesh Gunesekera and Chitra Banerjee Divakaruni and their novels Reef and The Mistress of Spices, which were both translated by the author. The novels reflect the social and political problems in Sri Lanka and India which make their citizens flee abroad. The stories are well narrated by poetic language and brought their authors international recognition. Especially the descriptive passages in both novels are very impressive and are considered here as specific language structures. A partial analysis of typical sentence elements of such passages in comparison with their Czech equivalents is the main aim of this article. Apart from that, a general comment on the main characters of the two stories and implications of different cultures are supplemented.